Occurrence and antimicrobial susceptibility of Staphylococcus aureus in dairy farms and personnel in selected towns of West Shewa Zone, Oromia, Ethiopia - Milsan Getu Banu; Endrias Zewdu Geberemedhin (PLoS ONE, 2022)
Staphylococcus aureus is one of the foodborne disease-causing bacterial pathogens. A cross-sectional study was conducted in selected towns of the West Shewa Zone, Oromia, Ethiopia from December 2020 to April 2021. The objectives of the study were to estimate the occurrence and load of S. aureus in raw cows’ milk, the antimicrobial susceptibility patterns of the S. aureus isolates, and assess the knowledge, attitude, and practice of the farmers on factors of antimicrobial resistance. A total of 311 samples from raw cows’ milk (212), milkers’ hands (44), and milking buckets (55) swabs were collected and tested. The disc diffusion method was used to test the antimicrobial susceptibility of the isolates. A questionnaire survey was conducted to assess the factors of milk contamination with S. aureus and antimicrobial resistance. The Chi-square test, one-way analysis of variance, and logistic regression analysis were used for data analyses. The result indicated that 16.72% (52/311) (95% CI: 12.75–21.34%) of the samples were positive for S. aureus. The occurrence of S. aureus was 22.73%, 16.51%, and 12.73% in milkers’ hand swabs, cow milk, and milking bucket swabs, respectively. The mean count of S. aureus from raw cows’ milk was 4.3± 1.45 log10 CFU/ml. About 88% of S aureus isolates were resistant to ampicillin while 82.9% and 70.7% of the isolates were susceptible to ciprofloxacin and cefotaxime respectively. The majority of the S. aureus isolates (61%) showed multi-drug resistance. The odds of S. aureus isolation from the milk of cows were significantly high in older cows (Adjusted Odds Ratio [AOR]: 5.54; p = 0.001), in late lactation stages (AOR: 3.6; p = 0.012), and in farms where house cleaning was done twice per week (AOR: 8.7; p = 0.001). A high percentage of farmers had insufficient knowledge, attitude, and practice (KAP) about the factors contributing to antimicrobial resistance. In conclusion, the poor milk hygienic practices, high rate of antimicrobial resistance (AMR), and inadequate KAP of farmers about factors of AMR suggest potential public health risks thus requiring training and surveillance programs.